Severity, extent, distribution and predisposing factors of gingival recession in Turkish patients: a cross-sectional study - Çelik, H.; Güngörmek, HS (Medicina oral, patología oral y cirugía bucal, 2025)
The aim of this cross-sectional study was to assess the extent, severity, distribution and potential predisposing factors of gingival recession (GR), utilizing a questionnaire and clinical periodontal measurements obtained from Turkish patients. A total of 534 subjects were examined. Participants meeting the inclusion criteria evaluated by dental hygiene habits, educational level, smoking habit and past orthodontic treatment. Plaque index (PI), gingival index (GI), probing depth (PD), bleeding on probing (BOP), clinical attachment level (CAL), gingival thickness (GT), high frenum attachment, and mobility were recorded on the tooth with GR. Probe transparency (PT), crown width/crown length ratio (CW/CL), papilla height (PH) and height of gingival scallop were measured on the index tooth (#11FDI). The GR severity was categorized by using Miller's classification. Of the 534 individuals examined in this study, 376 (70.4%) had gingival recession, while 262 patients (49%) were meeting the inclusion criteria and 2,721 teeth (37%) were affected. The majority of the teeth (44.8%) showed Miller class I. The highest GR frequency was detected in incisors (39.5%), particularly in mandible. The correlation between GR and PI (p=0.025), PD (p=0.034), PH (p=0.007), CW/CL (p=0.009), CAL (p<0,001), PT (p<0,001) was found statistically significant. No statistical relation was found between tooth brushing duration (p>0,05), tooth brushing frequency (p>0,05) and gingival recession. Gingival recession is a multifactorial condition significantly influenced by clinical and anatomical parameters such as PI, PH, CW/CL, PT while toothbrushing habits, including duration and frequency, appear to have a minimal impact.